José Antonio Primo de Rivera : the reality and myth of a Spanish fascist leader - Thomàs, Joan Maria (Berghahn Books, 2019)
"There are few individuals in modern Spanish history that have been as thoroughly mythologized as José Antonio Primo de Rivera, a leading figure in the Spanish Civil War who was executed by the Republicans in 1936 and celebrated as a martyr following the victory of the Falangists. In this long-awaited translation, Joan Maria Thomàs provides a measured, exhaustively researched study of Primo de Rivera's personality, beliefs, and political activity. His biography shows us a man dedicated to the creation of a fascist political regime that he aspired to one day lead, while at the same carefully distinguishing his aims from those of the Falangists and the Franco Regime"-- Provided by publisher.
Keywords: Primo de Rivera, José Antonio, -- 1903-1936.; Primo de Rivera, José Antonio, -- 1903-1936 -- Political and social views.; Falange Española de las J.O.N.S. -- Biography.; Primo de Rivera, José Antonio, -- 1903-1936; Falange Española de las J.O.N.S.; Statesmen -- Spain -- Biography.; Fascists -- Spain -- Biography.; Spain -- History -- Civil War, 1936-1939 -- Biography.; Fascism -- Spain -- History -- 20th century.; Spain -- Politics and government -- 1931-1939.; Hommes d'État -- Espagne -- Biographies.; Fascistes -- Espagne -- Biographies.; Fascisme -- Espagne -- Histoire -- 20e siècle.; Espagne -- Politique et gouvernement -- 1931-1939.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Europe -- Spain & Portugal.; BIOGRAPHY & AUTOBIOGRAPHY / Political; Fascism; Fascists; Political and social views; Politics and government; Statesmen; Spain; 1900-1999; biography.; dictator.; fascism in spain.; fascism.; hero worship.; historical biography.; history reference.; latin american history.; latin american studies.; politics.; savior of spain.; spain dictator.; spanish civil war.; spanish government.; spanish history.; world leaders.; Biography; Biographies; History; Biographies.